2023
DOI: 10.33271/mining17.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A new concept for complex mining of mineral raw material resources from DTEK coal mines based on sustainable development and ESG strategy

Abstract: Purpose. The research purpose is to develop a concept for complex mining of mineral resources from coal mines using the example of PJSC DTEK Pavlohradvuhillia mines with a transition to multi-product production of clean drinking water, utilization of methane, secondary coal from rock dumps and sludge reservoirs, low-potential thermal energy of mine groundwaters and associated raw materials from desalination waste. Methods. The research uses an integrated approach, which includes an analysis of existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The organizational concept is an approach to developing models and describing the processes of production complexes [23]- [25], focusing on the organizational structure and functions of the business system. This concept defines how different structural elements and their roles (functions) interact with each other within the framework of business processes.…”
Section: Figure 2 Promising Model Of the Infrastructure For Complex M...mentioning
confidence: 99%
“…The organizational concept is an approach to developing models and describing the processes of production complexes [23]- [25], focusing on the organizational structure and functions of the business system. This concept defines how different structural elements and their roles (functions) interact with each other within the framework of business processes.…”
Section: Figure 2 Promising Model Of the Infrastructure For Complex M...mentioning
confidence: 99%
“…Technological progress, the rapid decrease in prices of energy from renewable sources, and the need to drastically reduce greenhouse gas emissions clearly indicate the possibility of using hydrogen as a clean energy carrier [7,8]. Hydrogen can be produced from both renewable and non-renewable sources.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to selectively pump water with different degrees of mineralization. According to the Ukrainian experience, it would be possible to treat a part of the pumped water [7,39]. Excluding the cost of pumping, the cost of treating less mineralized waters from shallower depths will not exceed the purchase price of pure piped water.…”
Section: Introductionmentioning
confidence: 99%
“…The review of recent scientific works showed that the problem of the effective use of mineral depos its, in particular coal, is dealt with by technologists, ecologists and economists [1,2]. A coal mine as a natural resource con tains, in addition to coal, water, methane, and subsoil heat [3]. This applies not only to operating mines, but also to those be ing closed in order to transfer them to another economic plane.…”
Section: Introductionmentioning
confidence: 99%